2016
DOI: 10.1080/14737175.2016.1184086
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor therapy sequesters inflammation in affording neuroprotection in cerebrovascular diseases

Abstract: In recent years, accumulating evidence has demonstrated the important role of inflammation in cerebrovascular diseases. The inflammation can last for a long period after the initial insult. Hence, modulation of the inflammation in a wider therapeutic window is a practical approach to treat these cerebrovascular diseases. Despite the acute upregulation of many growth factors after the injury, it is not sufficient to protect and to regenerate the brain. In this mini review, we discuss major growth factors and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 139 publications
(174 reference statements)
0
14
0
Order By: Relevance
“…Stroke and TBI share some similar pathologies regarding the primary and secondary cell death mechanism largely resulting from chronic neuroinflammation . A key common pathological feature is the formation of a necrotic tissue core, which is unrecoverable, following stroke and TBI . The onset and progression of secondary cell death of both diseases has been linked to the blood‐brain barrier (BBB) breakdown, allowing various inflammatory cytokines to permeate the BBB, infiltrate the brain, and upregulate the inflammatory response, altogether worsening the disease outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke and TBI share some similar pathologies regarding the primary and secondary cell death mechanism largely resulting from chronic neuroinflammation . A key common pathological feature is the formation of a necrotic tissue core, which is unrecoverable, following stroke and TBI . The onset and progression of secondary cell death of both diseases has been linked to the blood‐brain barrier (BBB) breakdown, allowing various inflammatory cytokines to permeate the BBB, infiltrate the brain, and upregulate the inflammatory response, altogether worsening the disease outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…5 A key common pathological feature is the formation of a necrotic tissue core, which is unrecoverable, following stroke and TBI. [6][7][8] The onset and progression of secondary cell death of both diseases has been linked to the blood-brain barrier (BBB) breakdown, allowing various inflammatory cytokines to permeate the BBB, infiltrate the brain, and upregulate the inflammatory response, 9 altogether worsening the disease outcomes. In addition, several other exacerbating factors, such as oxidative stress, apoptosis, and mitochondrial dysfunction, have been shown to contribute to additional neurodegeneration following BBB damage.…”
mentioning
confidence: 99%
“…Numerous studies referenced throughout the articles have indicated the potential capability of stem cell therapy in regenerating the diseased brain. We are gaining more insights into the cellular death pathways mediating stroke [34][35][36][37][38][39], and in parallel exploiting these novel diseaserelated mechanisms as therapeutic targets for stem cells to exert their functional benefits. Yet, these developing technologies face obstacles, such as bioethical concerns and misrepresentations, as well as exploitations by the unscrupulous media and business sector, preventing them from reaching full beneficial capacity.…”
Section: Resultsmentioning
confidence: 99%
“…These neurotrophic factors generally confer therapeutic effects via their activation of cell survival pathways, yet TBI usually entails a decrease in their expression. In this respect, treatment intended to rescue these expression levels may circumvent the TBI‐induced apoptosis in the peri‐impact area . While preclinical studies of stroke have revealed that administering stand‐alone glial cell line–derived neurotrophic factor (GDNF), brain‐derived neurotrophic factor (BDNF), vascular endothelial growth factor (VEGF), stem cell factor (SCF), or stromal cell–derived factor (SDF)‐1α may produce improvements on neurological outcomes, various complications limit the likelihood of clinical success.…”
Section: Cell Therapy For Traumatic Brain Injurymentioning
confidence: 99%
“…Inappropriately high doses may do more harm than good; for example, drug‐induced overproduction of BDNF has been documented to trigger epileptic seizures . To this end, stem cells possess an innate ability to respond to the minute‐to‐minute status of their environment and adjust the levels of their secreted neurotrophic factors accordingly . By affording an in situ source for these factors, transplanted stem cells may reduce inflammation and increase cell survival.…”
Section: Cell Therapy For Traumatic Brain Injurymentioning
confidence: 99%